2012
DOI: 10.1063/1.4704344
|View full text |Cite
|
Sign up to set email alerts
|

Direct thrust force measurement of pulse detonation engine

Abstract: In this paper we present the result of High-Speed Reacting Flow Laboratory (HiREF) pulse detonation engine (PDE) experimental study on direct thrust measurement. The thrust force generated by the repetitive detonation from a 50 mm inner diameter and 600 mm length tube was directly measured using load cell. Shchelkin spiral was used as an accelerator for the Deflagration to Detonation Transition (DDT) phenomenon. Propane-oxygen at stoichiometric condition was used as the combustible fuel-air mixture for the PDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…It was further reported that the impulse fluctuated from 30 N•s up to 98.5 N•s for its 4s run at 1 Hz frequency. The average force was 61.5 N [17] which is in line with reports from similar research. In this PDE, as in many, there is a purge phase after the detonation that clears the PDE of exhaust gases and cools it as well.…”
Section: Shchelkin Spiralsupporting
confidence: 91%
See 1 more Smart Citation
“…It was further reported that the impulse fluctuated from 30 N•s up to 98.5 N•s for its 4s run at 1 Hz frequency. The average force was 61.5 N [17] which is in line with reports from similar research. In this PDE, as in many, there is a purge phase after the detonation that clears the PDE of exhaust gases and cools it as well.…”
Section: Shchelkin Spiralsupporting
confidence: 91%
“…Wahid et al [17] utilized a SS to assist in DDT was 50mm ID and 600 mm in length. The SS was 400 mm in length and with a reported blockage ratio of 43%.…”
Section: Shchelkin Spiralmentioning
confidence: 99%